Design and diffusion of systems for human benefit: toward more humanistic realisation of information systems in society - Venable, John; Pries-Heje, J.; Bunker, D.; Russo, N. (Emerald Group Publishing Limited, 2011)
PurposeThis paper introduces this special issue of IT&P on Systems for Human Benefit (S4HB), develops and promotes the idea of S4HB, and advocates that more research be conducted on the design and diffusion of S4HB. Design/methodology/approachThis conceptual paper argues that S4HB are systemically under-researched based on a historical perspective on IS research and proposes an agenda for research on the design and diffusion of S4HB. FindingsThe paper identifies extant areas of S4HB, such as health and education, but also advocates that new areas of S4HB be identified and new kinds of S4HB be designed. It further discusses how diffusion is a key issue to the realisation of human benefits and contrasts diffusion of S4HB with more commercial business systems as a motivator for further research. Finally it sets out a brief agenda for research in S4HB, including (1) development of a vision for research on S4HB that emphasises design for solving human problems (2) research on diffusion of S4HB, (3) revision of the way impact is assessed by journals to include assessment of the significance of the problem and the achievement of human benefit, and (4) promotion of a research culture, policies, and funding that emphasise S4HB.Originality/valueThis is the first paper to pull together a common perspective on the disparate areas of S4HB. The paper identifies what S4HB are, what their goals are, what areas are concerned, and sets out an agenda for what research is needed to realise them and their benefits in society.